STUDI PENGGUNAAN KITOSAN KOMPOSIT CuO SEBAGAI ADSORBEN UNTUK MENYERAP LOGAM BESI (Fe) MANGAN (Mn) DAN SENG (Zn) PADA AIR SUNGAI BELAWAN - Mutia Khairuni; Zul Alfian; Harry Agusnar (JURNAL KIMIA MULAWARMAN, 2017)
The synthesis of chitosan-CuO composite and its application as an adsorbent in the removal of Fe, Mn, and Zn in Belawan river water has been conducted. Chitosan-CuO composite is synthesized by addition the Cu(NO3)2 into the solution of chitosan and NaOH 2M. This adsorbent is characterized with FT-IR and its capability to adsorb heavy metals is measured with ICP-OES. The preliminary result of Fe, Mn, and Zn level in Belawan river water are 0,3032; 0,3251; and 0,06402 mg/L, respectively, those value levels are above the PP No. 82 Tahun 2004 safety limit. The optimum contact time of adsorbent to interact is found at 30 minutes, with Fe, Mn, and Zn adsorption is 69,71; 90,53; and 92,05%, respectively. The decrease of heavy metal levels in Belawan river water is influenced by the contact time of adsorbent to the sources of heavy metal.